CD27-CD38lowCD21low B-Cells Are Increased in Axial Spondyloarthritis - Wilbrink, Rick; Spoorenberg, Anneke; Arends, Suzanne; van der Geest, Kornelis S. M.; Brouwer, Elisabeth; Bootsma, Hendrika; Kroese, Frans G. M.; Verstappen, Gwenny M. (Frontiers in Immunology, 2021)
B-cells have received little attention in ankylosing spondylitis (AS) and for this reason their role in pathogenesis remains unclear. However, there are indications that B-cells may be involved in the disease process. Our objective was to obtain insights into the composition of the peripheral B-cell compartment of AS patients compared to healthy donors (HD) and patients with primary Sjögren’s syndrome (pSS), a typical B-cell-associated autoimmune disease. Special emphasis was given to CD27-negative B-cells expressing low levels of CD21 (CD21low B-cells), since this subset is implicated in autoimmune diseases with strong involvement of B-cells. Transitional B-cells (CD38hi) were excluded from the analysis of the CD27-CD21low B-cell compartment. This study included 45 AS patients, 20 pSS patients and 30 HDs. Intriguingly, compared to HDs the frequency of CD27-CD38lowCD21low B-cells was significantly elevated in both AS and pSS patients (P<0.0001 for both comparisons). The frequency of CD27-CD38lowCD21low B-cells expressing the activation-induced immune markers T-bet and CD11c was decreased in AS patients compared to HDs. A higher proportion of CD27-CD38lowCD21low B-cells expressed the chemokine receptor CXCR3 in AS compared to HDs, suggestive for active involvement of these cells in an inflammatory process. The frequency of CD27-CD38lowCD21low B cells in AS patients correlated positively with age and erythrocyte sedimentation rate. Furthermore, AS patients with extra-skeletal manifestations (ESM) showed increased frequencies of CD27-CD38lowCD21low B-cells compared to patients without ESM. In conclusion, our findings are suggestive of active B-cell involvement in the pathogenesis of AS, against prevailing dogma.